Prospects of engineered bacteria-assisted CAR T Cell therapy in gastrointestinal cancers - Zhang, Qingqing; Song, Xiao; Liu, Junhong; Zhou, Xuejiao (Oncology Reviews, 2025)
The high incidence and mortality rates associated with gastrointestinal cancers represent a significant global health challenge. In recent years, CAR T cell therapy has emerged as a promising immunotherapeutic approach, demonstrating favorable clinical outcomes. However, the application of traditional CAR T cell therapy in gastrointestinal cancers faces numerous challenges, including the suppressive tumor microenvironment and limitations in anti-tumor efficacy. The application of engineered bacteria offers a novel strategy to enhance CAR T cell therapy by modulating the tumor microenvironment and boosting immune responses, potentially leading to improved therapeutic outcomes. This review synthesizes the current research advancements related to engineered bacteria-assisted CAR T cell therapy in gastrointestinal cancers, exploring its underlying mechanisms, clinical applications, and future developmental directions.